Two‐year follow‐up of the MOSAIC trial: A multicenter randomized controlled trial comparing two psychological treatments in adult outpatients with broadly defined anorexia nervosa. Issue 8 (6th April 2016) - Schmidt, Ulrike; Ryan, Elizabeth G.; Bartholdy, Savani; Renwick, Bethany; Keyes, Alexandra; O'Hara, Caitlin; McClelland, Jessica; Lose, Anna; Kenyon, Martha; Dejong, Hannah; Broadbent, Hannah; Loomes, Rachel; et al.
ABSTRACT: Objective: This study reports follow‐up data from a multicenter randomized controlled trial ( n = 142) comparing the Maudsley Model of Anorexia Nervosa Treatment for Adults (MANTRA) with Specialist Supportive Clinical Management (SSCM) in outpatients with broadly defined anorexia nervosa (AN). At 12 months postrandomization, all patients had statistically significant improvements in body mass index (BMI), eating disorder (ED) symptomatology and other outcomes with no differences between groups. MANTRA was more acceptable to patients. The present study assessed whether gains were maintained at 24 months postrandomization. Methods: Follow‐up data at 24 months were obtained from 73.2% of participants. Outcome measures included BMI, ED symptomatology, distress, impairment, and additional service utilization during the study period. Outcomes were analyzed using linear mixed models. Results: There were few differences between groups. In both treatment groups, improvements in BMI, ED symptomatology, distress levels, and clinical impairment were maintained or increased further. Estimated mean BMI change from baseline to 24 months was 2.16 kg/m 2 for SSCM and 2.25 kg/m 2 for MANTRA (effect sizes of 1.75 and 1.83, respectively). Most participants (83%) did not require any additional intensive treatments (e.g., hospitalization). Two SSCM patients became overweight through binge‐eating. Discussion: Both treatments have value as outpatient interventions for patients with AN. © 2016 Crown copyright. International Journal of Eating Disorders. (Int J Eat Disord 2016; 49:793–800)